CARDIAC INVOLVEMENT IN CRITICALLY ILL COVID 19 PATIENTS: A SINGLE CENTER STUDY FROM PAKISTAN - Heeralal; Haidri, Fakhir Raza; Haq, Zakia; Kumar, Ramesh; Mehmood, Syed Aftab (Infectious Diseases Journal of Pakistan, 2022)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) causes a severe respiratory illness. Early studies suggest that COVID-19 can cause a wide range of cardiac complications. This prospective study was conducted to describe the cardiac abnormalities in patients with COVID-19 including cardiac enzymes, electrocardiogram, transthoracic echocardiographic findings and identifying the characteristics of different participant groups with positive and negative findings. Material and Methods: All consecutive adult patients admitted to the ICU with confirmed COVID19 infection were included in the study. Data were recorded on demographics, comorbidities, ECG findings, cardiac enzymes, and echocardiography findings. Data were analyzed using SPSS ver.26 and a p-value of ≤ 0.05 was considered significant. Results: A total of 129 patients were included with a median age of 53 years. High sensitivity troponin I was raised in 24.1% patients. Ischemic changes in electrocardiogram were found in 18.6% of the patients. Overall, 41.86% had some type of cardiac abnormality on echocardiography. This study found a significant association between the male gender and low ejection fraction (p-value of 0.019). This study also found a significant association between significantly raised troponin I and low ejection fraction (p-value 0.034). Overall, in-ICU mortality was 40.3% which does not differ significantly across normal and abnormal cardiac enzymes, ECG findings, and echocardiography groups. Conclusion: The male gender, and significantly raised trop I are risk factors for having a low ejection fraction. Abnormal cardiac parameters have no effect on in-ICU mortality. Keywords: Ultrasonography, Echocardiography, Troponin, COVID-19, Critical care